(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The basic characteristics of population health and the groups most sensitive to climate change in highland adolescents were identified. As a result of a comprehensive analysis, information databases of EEG parameters of adolescents living at an altitude of 2800 m above sea level were created. in Naryn, Osh and Issyk-Kul regions, with the identification of features of regional EEG standards, as well as the development of "electronic passports of the functional state of health" of adolescents living in the high- mountainous regions of these regions of the Kyrgyz Republic. It has been established that the high stability and plasticity of the central nervous system are the main physiological resources for effective behavior in the mountains, ensuring their adaptation and allowing to distinguish groups of individuals with an unstable functional state, exposed to adverse environmental influences.